Rheological Control of the Coffee Stain Effect for Inkjet Printing of Ceramics. Issue 7 (11th May 2013) - Friederich, A.; Binder, J. R.; Bauer, W.; Derby, B.
<x xml:space="preserve">Abstract</x> The rheology of inkjet printing inks must be well controlled in order to be able to form small droplets. One solution is to use low volume fraction dispersed suspensions, but this leads to a common problem during drying called the coffee stain effect. It is caused by particle migration from the center to the edge of a drying drop and leads to nonuniform printed structures. This article describes an approach, to suppress the coffee stain effect by a sufficiently fast increase in viscosity after deposition. Due to the viscosity limitations during printing, inks with tailored rheology and drying behavior need to be developed. Ceramic inks were prepared and printed. First, a binder was added to study the influence of viscosity on printability and the coffee stain effect. Second, the use of a high vapor pressure solvent for faster drying was investigated. Eventually, an ink with the combination of binder and fast drying agent was prepared. This ink showed a considerable decrease in drying time as well as a rapid increase in viscosity after deposition and was suitable to completely suppress the coffee stain effect. Plateau‐like structures were achieved by adapting the drying temperature to permit particle movement to a certain degree.